Modelling learning in economics - Brenner, Thomas, 1968- (E. Elgar, 1999)
"This book investigates the processes involved in economic learning by categorising different ways of learning, and using mathematical models for their description. The author distinguishes three types of learning processes - non-cognitive, routine-based and associative learning - and, for each of these, a model is proposed. Thomas Brenner also provides an overview of the psychological literature on learning and on the learning models most frequently used in economics."--BOOK JACKET. "This book will be of interest to economic psychologists and economists working in the areas of game theory, consumer and investment behaviour and the diffusion of innovation."--BOOK JACKET.